Characterization and Synthesis of Biocomposite Film with Coir and Polyvinyl Alcohol/Polyethylene Glycol - Vandna; Gond D.K.; Yadav B.K.; Priyadarshan S.; Yadav V.L. (My University, 2025)
This study explores the synthesis of biodegradable composite films by incorporation of different amounts of polyethylene glycol with polyvinyl alcohol, untreated coir and treated coir using the solution casting method. The effect of polyethylene glycol on the structure and properties of the synthesized biocomposite films was investigated. The increased ratio of polyvinyl alcohol/polyethylene glycol resulted in decreased tensile strength. This investigation revealed that the incorporation of 10 wt% polyethylene glycol with polyvinyl alcohol was sufficient to synthesize the biocomposite film and resulted in tensile strength of 28.14 MPa. It was observed that the incorporation of 30 wt% polyethylene glycol led to phase separation with the tensile strength of 18.33 MPa and hence, 10 wt% polyethylene glycol incorporation is best among the tested treatments for synthesizing biodegradable composite film. © 2024 National Institute of Science Communication and Policy Research. All rights reserved.